Isometry of potential attachment sites for the iliotrochanteric suture in dogs: An ex vivo study - Cintra, Cristiane Alves [UNESP]; Dias, Luís Gustavo Gosuen Gonçalves [UNESP]; Dias, Fernanda Gosuen Gonçalves; Ferreira, Danyelle Rayssa Cintra [UNESP]; de Freitas Pereira, Lucas; Rocha, Jessé Ribeiro; de Carvalho, Leonardo Lamarca; Selmi, André Luis (Universidade Federal do Rio Grande do Sul, 2021)
Background: Coxofemoral luxation is the most common traumatic luxation in dogs and the iliotrochanteric suture is one of the surgical treatment options. The orthopedic suture aimed at surgically restoring joint movement should be employed in an isometric manner in order to maintain adequate tension throughout the arc of motion. This study aimed to determine the isometric points for the iliotrochanteric suture in dogs during the joint extension and flexion movements. This evaluation was performed both in the intact hip joint and in the luxation model, establishing the best combination, among the determined points, for the reestablishment of normal joint movement. Materials, Methods & Results: Radiographic analyses of 12 canine cadaveric hips, both intact and in craniodorsal luxation model, were performed in a neutral position, flexion at 50°, and extension at 150°. In the trochanteric segment, two parallel lines were drawn, creating the central vertical axis and the secondary vertical axis. Three points were then determined on each axis, from proximal to distal, corresponding to 25, 50, and 75% of the height of the axis, and were labelled as T1, T2, and T3 and T4, T5, and T6, respectively. In the iliac segment, a line perpendicular to the longitudinal axis of the ilium was drawn, and 25, 50, and 75% of this height corresponded to points I1, I2, and I3, respectively. The lengths between the points were measured, with the objective of evaluating which combination of points presented less variation in the joint positions. The central location of the iliac and trochanteric segments, determined respectively by I2 and T2, provided smaller variations during the maximal movements of hip flexion and extension. Discussion: The surgical techniques of iliotrochanteric suture target to maintain the internal rotation of the femoral head inside the acetabulum and abduction of the femur until the soft tissues have healed. The described techniques for the iliotrochanteric suture present a great anatomical variety in the arrangement of the anchor points of the suture. It is known that if during motion, the attachment sites move closer to one another, the suture will become lax and, if the attachment sites move away from one another, the suture will tighten. Therefore, the implantation in isometric sites assists in reducing the variation of the distance between the points of origin and insertion of the suture during joint movement, keeping the suture tension constant and allowing the functional recovery of the joint. This study demonstrates that there are some locations for the origin and insertion of an iliotrochanteric suture that are associated with less length change than others. I2-T2 combination is the point closest to isometry for the iliotrochanteric suture during hip extension and flexion, so that, T2 is the most central point of the greater trochanter, corresponding to 50% of the height of its central vertical axis, as well as I2, which corresponds to the most central point of the ilium, representing 50% of the height of the most caudal portion of its body. The isometric point found by us details the exact location of perforation in all aspects (height and length), both in the ilium and the trochanter. In addition, it is a personalized point created for each patient from its radiographic examination and taking into consideration its anatomical variations, so that there is no damage to the suture during hip extension and flexion movements.
Keywords: Canine; Coxofemoral joint; Hip dislocation; Ilio-femoral suture; Joint instability; Orthopedics